Reinterpretasi Konflik NU-Muhammadiyah di Pedesaan Jepara Jawa Tengah - Arief Akhyat (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
Muhammadiyah and Nahdlatul Ulama (NU) are the biggest social and religious organization in Indonesia that have different types whether in the sense of the method of concluding the religious objectives, different ritual system especially in interpreting Islamic jurisprudence, and different attitudes in understanding a local tradition system. Moreover, both organizations have differences not only in ritual manner, but also impacted to many aspects such as in legitimating the social, cultural and political aspects. Therefore, the article is concentrated on the dynamics relation politically, religiously, and culturally between Muhammadiyah and NU in micro scale, particularly at certain village in Jepara. In conclusion, the writer assumes that a tension or conflict between Muhammadiyah and Nahdlatul Ulama in Jepara was a conflict concerning political interest. Keywords: Muhammadiyah, Nahdlatul Ulama, politics, conflict.